2016
DOI: 10.1016/j.jamcollsurg.2015.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons’ Leadership Styles and Team Behavior in the Operating Room

Abstract: Background The importance of leadership is recognized in surgery, but the specific impact of leadership style on team behavior is not well understood. In other industries, leadership is a well-characterized construct. One dominant theory proposes that transactional (task-focused) leaders achieve minimum standards, whereas transformational (team-oriented) leaders inspire performance beyond expectations. Study Design We video-recorded 5 surgeons performing complex operations. Each surgeon was scored on the Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 32 publications
1
60
0
5
Order By: Relevance
“…It remains unclear why female applicants received higher rankings compared to their male counterparts. Although the virtues of a team‐oriented approach within the operating room have recently been elucidated, a more authoritative, individualized approach to leadership remains more frequently employed by surgeons . Thus, applicants labeled “team players” may not be valued as highly within otolaryngology as well as other surgical fields as individuals described as “leaders.”…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear why female applicants received higher rankings compared to their male counterparts. Although the virtues of a team‐oriented approach within the operating room have recently been elucidated, a more authoritative, individualized approach to leadership remains more frequently employed by surgeons . Thus, applicants labeled “team players” may not be valued as highly within otolaryngology as well as other surgical fields as individuals described as “leaders.”…”
Section: Discussionmentioning
confidence: 99%
“…These findings contribute to the growing evidence base emphasizing leadership as an important skill for practising surgeons. A recent investigation has found that surgeons desire leadership training and that their leadership can transform team performance. It is now clear that patients can detect surgeons' leadership behaviours and think they are important.…”
Section: Discussionmentioning
confidence: 60%
“…The results show that patients' evaluations of non‐technical skills add meaningfully to their overall evaluation of service quality and are independent of evaluations of surgeons' empathy, a concept that also has a positive impact on patient satisfaction ratings. These findings contribute to the growing evidence base emphasizing leadership as an important skill for practising surgeons. A recent investigation has found that surgeons desire leadership training and that their leadership can transform team performance.…”
Section: Discussionmentioning
confidence: 74%
“…This includes the ability to set goals for and with staff under their domain and in other departments and the skills to work cooperatively and collaboratively with others. (35)(36)(37) Under the leadership of an experienced shift supervisor with skill in identifying and utilizing resources and allocating tasks to appropriate members of various departments, a hospital's senior management team can focus on the target task management and smooth operation of the ORs on an ongoing basis.…”
Section: Shift Supervisor-based Decision-makingmentioning
confidence: 99%